Treating cancer with cold physical plasma: On the way to evidence‐based medicine. Issue 5 (22nd January 2018) - Metelmann, Hans‐Robert; Seebauer, Christian; Rutkowski, Rico; Schuster, Matthias; Bekeschus, Sander; Metelmann, Philine
Abstract : The application of cold physical plasma in head and neck cancer patients is moving upwards in the pyramid of evidence‐based medicine (EBM). The effectiveness of plasma in cancer cell lines, cultivated human tumour cells, human tumour specimen freshly explanted from patients, animal model tumours, and animals with transplanted human tumour stem cells is well documented. There is consent among experts, referred to as EBM‐level IV, about the response to plasma in experimental settings and proof of concept by clinical pilot studies, EBM‐level III, for plasma treatment of head and neck cancer. If there is a manageable amount of tumour stem cells, like in precancerous lesions of oral mucosa or in small tumours like early basal cell carcinoma of the skin, plasma could become a clinical treatment option soon. Currently, it is already a concept in palliative care of patients with locally advanced head and neck cancer and contaminated ulcerations because of proven effectiveness against microbial pathogens. Patients greatly appreciate that plasma reduces strong fetid odour and pain while not being accompanied by serious side effects.